Capturing Secondary English Teachers' Teaching Style in the 21st Century: A Case Study at one Secondary School - Ridha Mardiani; Sifa Prasasti (Biormatika : Jurnal ilmiah fakultas keguruan dan ilmu pendidikan, 2023)
The demand of teaching in the 21st century has centered on the four Cs, critical thinking, creativity, collaboration and communication. How English teachers become aware of these characteristics and adapt their teaching styles to this demand needs to be researched. Therefore, this study aimed to (1) investigate the types of two English teachers teaching styles and (2) find out whether the teaching styles are still relevant to the 21st century teaching. This study employed a qualitative case study with descriptive data analysis. The study was conducted in one secondary school in Cimahi with two English teachers as participants. Two techniques were used in obtaining the data: 1) classroom observation, and 2) teachers’ interviews. Data were analysed in the lense of teaching style types from Grasha (1996), then juxtapose with the characteristics of learning in 21st century. The findings showed that T1 applied formal authority teaching style, while T2 implemented personal model category. T2 is more adaptable to the challenges of English teaching in 21st century by facilitating the students to be more critical in thinking, discussing current learning issues, helping the students using learning media proficiently and solving learning problems by collaborating and co-creating in real and virtual world